Współczesne studia nad Diodorem Sycylijskim - Andrzej Dudziński (In Gremium. Studies in History, Culture and Politics, 2021)
The aim of the article is to present the Polish reader with a brief outline of the current discussions in the field of the studies of Diodorus Siculus’ “Bibliotheke Historike” – one of the most important sources for studying ancient history. In the first part, the article discusses the main publications in the fields – including especially monographs on Dodorus and his work, editions and translations, and commentaries to individual books or groups of books.The second part offers an overview of the main research areas within the Diodorean studies. Among these, the attempts to identify and reconstruct the sources used by Diodorus (Quellenforschung) still feature prominently. However, in recent years this approach has been a subject of an extensive critique and consequently evolved into a more balanced view, even among the scholars who still argue for its crucial role in studying “Bibliotheke”. In the last decades the scholars turned their attention also to various themes and motifs which appear consistently throughout the whole oeuvre, most often reflecting Diodorus’ focus on the moral and didactic role of history.Another category of problems receiving a lot of attention in the recent years refers to the process of writing of “Bibliotheke Historike”. Both the dating of this process and its internal organization, and Diodorus’ method of work have been subjects of a lively discussion. The modern scholars are interested not only in Diodorus’ plan and its execution, but also in his stylistic and narrative choices, such as his decision to avoid lengthy speeches or his use of advanced rhetorical techniques.